2013
DOI: 10.1111/jpm.12064
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the experience of Canadian registered psychiatric nurses: a phenomenological study

Abstract: This paper describes a phenomenological study that was conducted in 2012 and investigated the experiences of registered psychiatric nurses working in the province of Manitoba. Ten registered psychiatric nurses participated in semistructured, audio-recorded interviews, during which they described their experiences, yielding written protocols that were thematically analysed. Results from this study revealed six predominant themes that included (1) perception of psychiatric nursing; (2) patient aggression; (3) pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The involvement of families in the treatment of their loved ones also shapes the social dynamics of care. One study of Canadian psychiatric nurses found that family members' sense of entitlement, confrontational behaviour, and many demands contribute to nurse frustration and fatigue [43]. The same results identified a disparity between family expectations and the medical realities surrounding the patient's circumstances, needs, and prognosis.…”
Section: Background Social Relations Of Nursing: Hierarchy Interactio...mentioning
confidence: 99%
See 1 more Smart Citation
“…The involvement of families in the treatment of their loved ones also shapes the social dynamics of care. One study of Canadian psychiatric nurses found that family members' sense of entitlement, confrontational behaviour, and many demands contribute to nurse frustration and fatigue [43]. The same results identified a disparity between family expectations and the medical realities surrounding the patient's circumstances, needs, and prognosis.…”
Section: Background Social Relations Of Nursing: Hierarchy Interactio...mentioning
confidence: 99%
“…When nurses tried to work through these differences in perception, family members were reported to sometimes belittle nurses' judgment of the situation and called on physicians to support what family members believed was the proper course of action for the patient. The participating psychiatric nurses also remarked on how patients' families tend to project and misplace their emotions onto nurses [43,44]. Relational tensions, alongside problems related to a lack of medical and healthcare resources available to nurses, can exacerbate strained communication practices between nurses and family members [45].…”
Section: Background Social Relations Of Nursing: Hierarchy Interactio...mentioning
confidence: 99%
“…In Canada, psychiatric nursing is a distinct regulated nursing profession in British Columbia, Alberta, Saskatchewan, and Manitoba (Jackson & Morrissette, 2014), and practitioners use the title of registered psychiatric nurse (RPN). From the province of Ontario, and in all provinces east to Newfoundland and Labrador, nurses who work with patients in mental health care settings are registered nurses (RNs).…”
Section: Brief History Of Psychiatric Mental Health Nursing Education...mentioning
confidence: 99%
“…Respecting a service users' decision is sometimes not feasible because it would go against the house rules based on the service users' collective preferences (Oeye et al, 2009) or result in harmful situations for other service users. For example, one service user's decision not to take medication to reduce aggressive behavior could hinder the safe and calm environment for other service users (Jackson & Morrissette, 2014). Sometimes service users' wishes go against the personal values of professionals and are therefore restricted (Pelto-Piri et al, 2013) and in some situations professionals take over when they consider the user unable to assume responsibility for their actions.…”
Section: Service Users' Experiences With User-user Participation In Dmentioning
confidence: 99%
“…Professionals, in turn, report that family carers sometimes demand granting service users' decisions when professionals feel this would lead to harmful situations. For instance, letting a service user stop a pureed diet when professionals fear this might lead to another choking incident (Jackson & Morrissette, 2014).…”
Section: Service Users' Experiences With User-user Participation In Dmentioning
confidence: 99%